The Invasive Macroalga Rugulopteryx okamurae: Substrata Plasticity and Spatial Colonization Pressure on Resident Macroalgae - García-Gómez, José Carlos; Florido, Marta; Olaya-Ponzone, Liliana; Sempere-Valverde, Juan; Megina, César (Frontiers in Ecology and Evolution, 2021)
The present study constitutes the first evaluation of the space colonization strategies performed by Rugulopteryx okamurae when co-occurring with the resident macroalgal community in the introduced areas. Since the first apparition of the non-indigenous macroalga in the Strait of Gibraltar, its high propagation capacity together with its colonization ability have enhanced the establishment success of the species in detriment of the resident biota. In this study, we carried out observational surveys during 2017-2020 in order to assess the coverage levels of R. okamurae on different lighting conditions, surface orientations and substrata types (artificial and natural). Results revealed that, beyond the high percent coverages already reported at illuminated and semi-illuminated natural rocky habitats, R. okamurae is able to settle on a wide variety of artificial substrata. The settlement performance of the species was also investigated and different mechanisms underlying the space colonization were proposed. Thus, R. okamurae was observed interacting with 43 resident macroalgal species at generally illuminated rocky habitats of the northern Strait coasts. Six colonization mechanisms were proposed for spatial growth scenarios. Overall, results pointed out that, in most of the cases where the invasive species co-occur with the resident community, R. okamurae would be favoured as regards spatial growth success. Competitive interactions and environmental factors which influence results obtained must be addressed in order to full predict impacts on resident communities. Moreover, together with previous scientific works, the overall data provided in this study highlight the need to urgent implement management measures focused on habitats susceptible to be invaded, as well as studies on the ecology and dispersal vectors of R. okamurae in the Strait of Gibraltar and adjacent areas.